If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 8 = 18x + -7 Reorder the terms: 8 + 13x = 18x + -7 Reorder the terms: 8 + 13x = -7 + 18x Solving 8 + 13x = -7 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 8 + 13x + -18x = -7 + 18x + -18x Combine like terms: 13x + -18x = -5x 8 + -5x = -7 + 18x + -18x Combine like terms: 18x + -18x = 0 8 + -5x = -7 + 0 8 + -5x = -7 Add '-8' to each side of the equation. 8 + -8 + -5x = -7 + -8 Combine like terms: 8 + -8 = 0 0 + -5x = -7 + -8 -5x = -7 + -8 Combine like terms: -7 + -8 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 3(x+4)+23=-4x | | 6g^3-23gh+15h^2=0 | | 16y^2+8yz-3z^2=0 | | x-14=-24 | | 2x-1.5=6 | | 2x^2+6y^2+3=4x^2-8y+4 | | 6(x-2)=-3x+42 | | 2+4x=x+11 | | 5x-3(x-1)-7=2(x-2) | | 4t+9+(2t+7)= | | -6=6+k | | -3(x-4)+7=-2x | | (4x^2-3x)(6x+5)=0 | | 3x-25=11x-5+2x | | 5(x-3)=2x+21 | | 5y+2x=25 | | 26+4y-4=16y-13-5y | | 3x-0.25y=-2 | | x+0.20(3)=0.60(x+3) | | 22x+8-24x=7-9 | | 6-(5p+3)=6[(5p-3)-(p-7)] | | -4x+16=-11x+10 | | 10x+9-9x=15 | | x=-14-3x | | -10+18=m-9 | | -15=5(3q-10) | | -3x-5=5+2x | | -3t-4=7 | | -8x+10=-x+80 | | 7x=-47 | | 3(6+8R)-3(R+2)= | | 4k^2+26k-36=0 |